Morphometric features of the prostate gland in rats with sulpiride-induced hyperplasia after combined administration of vitamin D and saw palmetto fruit extract - N.O. Tkachenko; O.S. Protsenko; N.O. Remnyova; L.I. Chumak; N.P. Smolienko; І.O. Bielkina; І.O. Marakhovskyi; Y.M. Korenieva; V.O. Bondarenko (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. The polyetiological nature, pathological changes in the structure of the prostate gland (PG), and various side effects resulting from prolonged use of certain prostate protectors, as well as the significant deterioration of menʼs health caused by the stressful conditions of modern life, encourage researchers to seek new approaches for the treatment and prevention of benign prostatic hyperplasia (BPH).